2015
DOI: 10.1186/s13075-015-0860-6
|View full text |Cite
|
Sign up to set email alerts
|

The specificity of anti-carbamylated protein antibodies for rheumatoid arthritis in a setting of early arthritis

Abstract: IntroductionAnti-carbamylated protein (anti-CarP) antibodies have been described in rheumatoid arthritis (RA) and arthralgia patients at risk of developing RA. To what extent these autoantibodies are specific for RA is unknown. Therefore, we investigated the diagnostic performance of the presence of anti-CarP antibodies for RA in a setting of early arthritis.MethodsAnti-CarP antibodies were detected using carbamylated fetal calf serum as substrate. Anti-CCP2 antibodies were measured using enzyme-linked immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 18 publications
8
46
1
Order By: Relevance
“…Recently, Shi et al investigated the diagnostic performance of anti-CarP in RA in a large cohort of patients with early arthritis and demonstrated that these antibodies are predominantly detected in RA, but that a small percentage of patients with almost all forms of early arthritis were also anti-CarP-positive [19]. Considering the high prognostic and predictive value that anti-CarP have demonstrated in patients with RA, the aim of this study was to evaluate their prevalence, sensitivity and specificity in a large monocentric cohort of patients with RA compared to other autoimmune rheumatic diseases (AIRDs).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shi et al investigated the diagnostic performance of anti-CarP in RA in a large cohort of patients with early arthritis and demonstrated that these antibodies are predominantly detected in RA, but that a small percentage of patients with almost all forms of early arthritis were also anti-CarP-positive [19]. Considering the high prognostic and predictive value that anti-CarP have demonstrated in patients with RA, the aim of this study was to evaluate their prevalence, sensitivity and specificity in a large monocentric cohort of patients with RA compared to other autoimmune rheumatic diseases (AIRDs).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is the first providing independent replication of the association between anti-CarP antibodies and radiographic progression within the ACPA-negative population in a large cohort of patients with RA with longitudinal radiographs over 8 years. Anti-CarP antibodies are predominantly present in RA with the reported sensitivity and specificity for RA of 44% and 89%, respectively 26. Intriguingly, already in the presymptomatic individuals the presence of anti-CarP antibodies is associated with RA development in ACPA-negative individuals and also with worse radiological progression independent of ACPA 15.…”
Section: Discussionmentioning
confidence: 99%
“…neutrophil enzymes that localize to NETs induce posttranslational modifications, such as citrullination and carbamylation, thus creating neoantigens that lead to anti-citrullinated protein autoantibodies (ACPA) and anti-carbamylated protein autoantibodies (ACarPA) (22)(23)(24)(25)(26). Given the abundance of nucleic acids in NETs, the induction of autoantibodies by NETosis is likely to be facilitated by TLR 7/9-mediated B cell activation (27).…”
Section: Introductionmentioning
confidence: 99%